Work-related musculoskeletal injuries amongst obstetrics and gynaecology trainees in East Midland region of the UK - Arslan Okuyucu, Kubra (Arch Gynecol Obstet, 2017)
PURPOSE: Work-related musculoskeletal injuries (WRMSI) have been well known amongst obstetrics and gynaecology (O&G) practitioners, but limited data have been reported. Our aim is to determine the prevalence, severity and characteristics of WRMSI amongst O&G trainees. METHODS: A musculoskeletal ergonomic survey was conducted amongst the O&G trainees in the East-Midlands region of United Kingdom (UK). The survey comprised of demographic details, year of training, previous manual handling training, any work-related orthopaedic injury, the type of injury, any treatment received in addition to any sick leave incurred after the injury were also documented. RESULTS: The response rate for the survey was 76% (59/78). The majority (22%) were senior specialist trainee, seventh year (ST7) and between 30 and 34 age groups. Approximately 90% of the trainees reported to have experienced pain in the last year. The most common site was the back, which was followed by the shoulders and the upper limbs. 63% of trainees reported injuries that were attributed to WRMSI. One in ten of the trainees needed time off work due to injury. A total of 20 days were lost in the last 12 months as a result of pain or discomfort attributed to obstetric work. CONCLUSIONS: Our results demonstrate the prevalence of work-related injuries and its detrimental effects. Such injuries are underreported on incident reporting system. Ergonomics and WRMSI prevention in obstetrics and gynaecology is an area seldom discussed. Obstetric training sessions should incorporate ergonomic interventions. Further research is required to establish relevant aetiological factors related to WRMSI in this specialty.